全球化背景下藏族农村社区的 语言生活——青海省黄南藏族 自治州力加村语言使用及语言 态度研究 = The Language Life in a Tibetan Village Community with Globalization: Case Study on Language Use and Attitude in Lijia Village, Huangnan, Qinhai - Chunlin, Yao (Sinología hispánica. China Studies Review, 2015)
采用问卷调查、辅以访谈的方式，调查藏 语安多方言区的一个农业社区（力加村）的语 言生活、语言活力、语言使用和语言态度。结 果显示，当地藏语文活力旺盛，藏语是当地各 种场合的主要交际用语。被调查对象中近一半 人是藏汉双语人，他们大多年龄较小或受过教 育。被调查对象的语言文字态度具有较强的包 容性，对藏汉语文都持积极态度。所有被调查 对象都希望后代接受藏语教育，近一半被调查 对象希望后代在接受藏语教育的同时接受汉语 和（或）英语教育。被调查对象对藏语具有很 强的民族情感。他们承认藏语文在当地活力旺 盛，但仍旧担心“政府制定的语言文字政策执 行不到位”会影响当地的藏语文发展。 In order to study language vitality, language use and language attitude in a Tibetan agriculture community (Lijia Village) in Amdo dialect region, the research methods Questionnaire and Interview are used to collect data. The research finds that the Tibetan Language which is the main communication language in local area is full of vitalities. All subjects hope their children access Tibetan education. At the same time, half of the subjects hope their children access Chinese or (and) English education and become bilingualism. The research also finds that half of the subjects are Chinese-Tibetan bilingualism, who are young and (or) educated; and most of the subjects hold the positive attitudes towards both Chinese and Tibetan